SPATIAL PLANNING BASED ON LOCAL WISDOM IN THE SAMBORI INDIGENOUS COMMUNITY THROUGH MANAGEMENT OF ETNO TOURISM POTENTIAL - Ardiansyah, Suriadi; Maryani, Enok (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2022)
The development of the population, which is accompanied by an increase in human needs in various aspects, causes various spatial problems. Spatial problems include settlements and unhealthy community environments such as slums, prone to floods, droughts, fires, pollution and damage to the environment, joblessness, and the spread of various diseases. Therefore, it is necessary to have a spatial arrangement that is in accordance with the needs and capacity of the space, so that a beautiful, cool and harmonious life can be achieved. Basically, the concept of spatial planning, ideally, has long been known by elements of Indonesian society, even before the explosion of population growth that occurs today. The existence of sacred spaces, areas, and land that are not allowed to build houses, residential areas in groups, areas for graves, areas for roads, areas for places of worship, agricultural areas, are forms of local spatial planning known to the general public. Local wisdom is one of the community’s capital to combine aspects of nature conservation with aspects of economic fulfillment which is conceptualized as Ethno tourism. One of the potentials that many regions have in Indonesia is the natural potential which because of its beauty and uniqueness can be developed for Ethno tourism. A very close correlation between local wisdom and ecotourism is that the local wisdom of a particular community is usually related to the way it relates to the environment and the natural surroundings. The interaction of this wisdom is a very good attraction to be packaged into a unique ecotourism concept. Based on the conceptual description of the analysis and the empirical conditions. It seems that the implementation of local spatial planning is one of the most fundamental alternatives to be presented in a scientific format so that we can understand more deeply the spatial concept built by our ancestors. Moreover, in the era of globalization which presents a very strong influence on all dimensions of life, including spatial planning, thus requiring us to have a strong foundation in managing space as a place to live and develop. This is where local values in managing spatial planning are needed to strengthen the identity and independence of the Indonesian nation. One of the villages in the Bima Regency that is able to maintain the traditions and local values of the Indonesian people’s spatial planning is the Sambori Traditional Village community. The Sambori community has used a spatial plan that is very in line with the values and spatial patterns in ecotourism management that is rational and in accordance with its ideal designation.